TINJAUAN ATAS PENYUSUNAN LAPORAN OPERASIONAL PADA BADAN KEUANGAN KABUPATEN NGAWI TAHUN 2020 - Aura Kharisma Putri, Mahasiswa (2022)
Based on Gurbernur Regulation Number 2 of 2017 concerning Amendments to Gurbernur Regulation Number 93 of 2014. The regulation regulates the "Accounting Policy of the East Java Provincial Government" in the governor's regulation stipulating that financial statements must have components consisting of: (1) Budget Realization Report; (2) Report on Changes in Over Budget Balance (SAL Change Report); (3) Balance sheet; (4) Operational Report (LO); (5) Cash Flow Statement (LAK); (6) Report on Changes in Equity (LPE); (7) Notes to Financial Statements (CaLK). The purpose of this writing is to find out the practice of preparing, presenting, disclosing, and comparing operational reports from the Ngawi Regency Regional Government. The method used in this writing is the Literature Study method, which is a method of collecting data by collecting by reading and studying information related to the topic to be discussed. The results obtained are the Preparation, presentation of disclosures, and comparisons of Operational Reports are appropriate, the Ngawi Regency Regional Government 2020. Keywords: Operational Report, Ngawi Regency Regional Government, Governor Regulation 2 of 2017.